Blockchain technology in the banking sector: a content analysis - Sheikh, Rafsun; Miah, Shah J.; Skinner, James; Cook, Peter (Frontiers in Blockchain, 2025)
IntroductionApplications of Blockchain technology (BT) offer transformative innovations in organizations. Because of its effectiveness as an intermediary-free platform, researchers consider this technological platform to adopt disruptive developments. In banking sector, BT has been adopted massively for significant disruptions, but their landscape of studies to develop general understanding are still at its emergent stage, therefore it is imperative to define existing landscape of BT for greater benefits in the research community. This paper examines existing studies of BT adoption in banking sector, with a special focus to reveal on how BT architectures can bring disruptions.MethodsThe analysis has scrutizised 214 relevant articles from peer-reviewed journals across four vital databases (coverage from 2021 to 15 July 2025), through an intelligent review that represents a combined iterative approach adopting both methods of Latent Dirichlet Allocation (LDA) topic modelling and content analysis.ResultsFrom an information systems viewpoint, the study divided the findings into three phases: pre-adoption, adoption, and post-adoption, highlighting blockchain’s dimensions, applications in banking, the current banking landscape, and the challenges that inhibit widespread adoption of BT in banking systems.Discussion/ConclusionThe synthesized findings indicate interesting directions for future research.